CARA-CARA PENYELESAIAN SENGKETA JUAL BELI BARANG SECARA INTERNASIONAL - Siregar, Naek (FIAT JUSTISIA)
International trade in particular the sale of international goods plays an important role in the economic growth process in addition to affecting directly and indirectly on the course of the overall economy. Therefore, countries have always tried to conduct international trade Buying and selling international goods pose legal problems because the parties in this activity have differences in legal systems, giving rise to the question of state law which applies to the contract between them. This issue becomes complicated menakala in the execution of the contract a dispute, and this dispute must be resolved by means of international dispute settlement.Â Keywords: Settlement of dispute, the Sale and Purchase of Goods International